2021
DOI: 10.1021/acs.jcim.1c00973
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Access Mechanism in a Novel Membrane-Bound Phospholipase A of Pseudomonas aeruginosa Concordant with Specificity and Regioselectivity

Abstract: PlaF is a cytoplasmic membrane-bound phospholipase A 1 from Pseudomonas aeruginosa that alters the membrane glycerophospholipid (GPL) composition and fosters the virulence of this human pathogen. PlaF activity is regulated by a dimer-to-monomer transition followed by tilting of the monomer in the membrane. However, how substrates reach the active site and how the characteristics of the active site tunnels determine the activity, specificity, and regioselectivity of PlaF for natural GPL substrates have remained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(73 citation statements)
references
References 113 publications
9
64
0
Order By: Relevance
“…ASMD tackles this problem by dividing the reaction path into smaller segments called stages . Within these stages, the trajectory closest to the Jarzynski average is determined, and the final state of this trajectory is used as starting point for the consecutive stage . Thus, trajectories contributing little to the overall PMF are disregarded in the next stage, that way reducing the total number of simulations to be performed.…”
Section: Methodsmentioning
confidence: 99%
“…ASMD tackles this problem by dividing the reaction path into smaller segments called stages . Within these stages, the trajectory closest to the Jarzynski average is determined, and the final state of this trajectory is used as starting point for the consecutive stage . Thus, trajectories contributing little to the overall PMF are disregarded in the next stage, that way reducing the total number of simulations to be performed.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, it has been suggested that this tilting motion underlies the activation of the monomeric PlaF by facilitating substrate access to the active site tunnel (5). In addition to the previously mentioned tunnel (T1), two other tunnels (T2 and T3) were identified, connecting the active site to the surface of PlaF (11). Unbiased MD simulations showed that myristic acid (MYR), the hydrolysis product of 1-myristoyl-2-hydroxy-sn-glycerol-3-phosphoglycerol (2LMG), a lysophospholipid, relocates from T3 and reaches the entrance of T1.…”
Section: Introductionmentioning
confidence: 94%
“…For each of the three systems, 12 replicas were performed, and binding and unbinding events of the FFA were monitored (Figure 6A). We identified an FFA as "bound" if it is within a distance < 15 Å from the T3 entrance (COM of residues K170, Q234, Y236) and has an RMSD < 1.5 Å to the previous pose (see Supplementary results) (11). Density maps of FFAs around t-PlaF show that FFAs tend to gather in T3, which connects the catalytic center to the periplasmic space (Figure 6B).…”
Section: Hot Spots Of D-plaf -Ffa Interactions In the Upper Leafletmentioning
confidence: 99%
See 2 more Smart Citations